2013
DOI: 10.1104/pp.113.214114
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of the Role of Carboxylic Acids in Metabolite Signaling in Arabidopsis Leaves    

Abstract: The transcriptional response to metabolites is an important mechanism by which plants integrate information about cellular energy and nutrient status. Although some carboxylic acids have been implicated in the regulation of gene expression for select transcripts, it is unclear whether all carboxylic acids have the same effect, how many transcripts are affected, and how carboxylic acid signaling is integrated with other metabolite signals. In this study, we demonstrate that perturbations in cellular concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 92 publications
3
57
1
2
Order By: Relevance
“…Instead, our data for daily sucrose oscillations and KfPRR7, KfPRR37, KfTOC1-1, and KfGI transcript regulation support the proposal that the pathway of metabolic regulation suggested to integrate photosynthetic sugar metabolism with the clock in Arabidopsis plays a role in the partial loss of rhythmicity observed in this K. fedtschenkoi rPPCK1-3 line (Haydon et al, 2013). Alternatively, malate changes in the rPPCK1-3 line may influence the clock, as malate has been demonstrated to function to influence gene regulation (Finkemeier et al, 2013).…”
Section: Impact Of Silencing Kfppck1 On Circadian Rhythms Of Cam Co 2supporting
confidence: 70%
“…Instead, our data for daily sucrose oscillations and KfPRR7, KfPRR37, KfTOC1-1, and KfGI transcript regulation support the proposal that the pathway of metabolic regulation suggested to integrate photosynthetic sugar metabolism with the clock in Arabidopsis plays a role in the partial loss of rhythmicity observed in this K. fedtschenkoi rPPCK1-3 line (Haydon et al, 2013). Alternatively, malate changes in the rPPCK1-3 line may influence the clock, as malate has been demonstrated to function to influence gene regulation (Finkemeier et al, 2013).…”
Section: Impact Of Silencing Kfppck1 On Circadian Rhythms Of Cam Co 2supporting
confidence: 70%
“…A metabolite analysis revealed that DIC substrates such as succinate and citrate are significantly reduced within 10 min of spray treatment, indicating that such rapid transcriptional responses occur to address a physiological change. Citrate is also known to trigger specific transcriptional response, but the target genes appear not to overlap with our findings, and the timeframe of 8 h used in these experiments is different (Finkemeier et al, 2013).…”
Section: Discussioncontrasting
confidence: 48%
“…Indeed, addition of citrate led to AOX induction in soybean and tobacco (Vanlerberghe and McLntosh, 1996;Djajanegara et al, 2002;Gray et al, 2004). In Arabidopsis, induction of AOX1a by citrate treatments could not be confirmed, and the changes observed were either modest or absent (Ho et al, 2008;Finkemeier et al, 2013). Overall, the transcriptomic effects of externally supplied citrate in Arabidopsis are mild compared to those observed in tobacco and soybean (Djajanegara et al, 2002;Gray et al, 2004).…”
Section: Responses To Mitochondrial Energy Signaling At the Transcripmentioning
confidence: 99%